PERKAWINAN DALAM HUKUM ADAT BADUY DAN PERKAWINAN DALAM KOMPILASI HUKUM ISLAM - Muslih, Muhammad (Journal of Islamic Law Studies, 2021)
This research explains about marriage regulated in Baduy traditional law and marriage regulated in Islamic Law Compilation (KHI). This research uses the Normative Sociological and Juridical Empirical research methods. This research is descriptive analytical and uses Primary Data Sources and Secondary Data Sources. Sources of data used were obtained from Library Research. Interviews of the Baduy community and field observations to the Baduy area were also carried out to obtain the data needed for this research. The results of this study indicate that there are many differences between the existing marriage regulations in Baduy customary law and the marriage regulations that have been regulated in the Compilation of Islamic Law (KHI). Some of these differences include that the Baduy people do not know polygamy and polyandry, there is no divorce, there is an early marriage (there is no age limit for marriage), and some of them register a marriage. Even though the Compilation of Islamic Law has regulated and facilitated polygamy and polyandry, divorce, marriage age limits, and marriage registration. The marriage of the Baduy people who hold fast to the ancestral customs of the ancestors with a very simple unwritten customary regulation turns out to be effective for the Baduy community. Compilation of Islamic Law that was compiled, codified, and deliberated by scholars brought in from all regions of Indonesia and applies nationally there are still people who do not obey it. This is inseparable from compliance, public awareness, legal awareness, and the number of people bound by these regulations.